Fe K-edge X-ray absorption spectroscopy study of Pb(Fe2/3W 1/3)O3-PbTiO3 multiferroic ceramics - Mesquita, A. [UNESP]; Fraygola, B. M.; Mastelaro, V. R.; Eiras, J. A. (AIP Publishing, 2013)
The present paper is a comprehensive study concerning Fe K-edge X-ray absorption spectroscopy (XAS) measurements, which were performed to characterize the local structure of (1 - x)Pb(Fe2/3W1/3)O 3-xPbTiO3 samples as a function of temperature and PbTiO3 content. Results obtained by the fits of extended X-ray absorption fine structure consist with rhombohedral symmetry for Pb(Fe 2/3W1/3)O3 composition at temperatures lower than room temperature. This result is in apparent disagreement with X-ray and neutron diffraction characterization which have been reported. This apparent disagreement is related to the fact that XAS probes the short-range order, whereas X-ray diffraction provides structural information about the average structure. Moreover, as the PbTiO3 content increases, a disorder has been detected at local structure of the FeO6 octahedron. Analysis of X-ray absorption near edge structure spectra did not show modifications in intensity nor energy of transitions. © 2013 American Institute of Physics.
Keywords: Average structure; Extended X-ray absorption fine structures; Multiferroic ceramics; Rhombohedral symmetry; Short range orders; Structural information; X-ray absorption near-edge structure; X-Ray and neutron diffraction; Absorption spectra; Extended X ray absorption fine structure spectroscopy; Neutron diffraction; X ray absorption near edge structure spectroscopy; X ray absorption spectroscopy; X ray diffraction; Lead